Unmethylated CpG motif-containing genomic DNA fragment of Bacillus calmette-guerin promotes macrophage functions through TLR9-mediated activation of NF-κB and MAPKs signaling pathways. Issue 3 (April 2020) - Li, Junli; Fu, Lili; Wang, Guozhi; Subbian, Selvakumar; Qin, Chuan; Zhao, Aihua
The potency of synthetic CpG-oligo-deoxynucleotides (CpG-ODNs) adjuvants in modulating the immune cell functions through the TLR pathway has been tested and reported previously. However, the cellular signaling involved in the stimulation of macrophages by natural, CpG motif-containing adjuvant and the effector functions modulated by such stimulation has not been well studied. Here, we used in vitro and ex vivo murine macrophage assay systems, and mouse model of in vivo stimulation to explore the signaling pathway and the effector functions mediated by BC01. Results show that BC01 can induce the production of TNF-α and MCP-1 in macrophages by up-regulating the activation of NF-κB and MAPKs signaling pathway, and elevated the expression of MHC-II, CD40, CD80, and CD86. Upon stimulation with BC01, the peritoneal macrophages isolated from TLR9 −/− mice produced significantly low levels of pro-inflammatory cytokines, attenuated the activation of NF-κB and MAPKs signaling pathways, and showed reduced phagocytosis. Following in vivo stimulation with BC01, the TLR9 −/− mice produced significantly lower levels of pro-inflammatory cytokines in the serum and lymph nodes showed reduced cell proliferation. These results indicate that BC01 is an efficient agonist of TLR9 that can significantly enhance the host-protective immune functions of macrophages.